Neural Correlates of Object and Verbal Cognitive Style during Task Switching - 오윤경; Chobok Kim (Korean Journal of Cognitive and Biological Psychology, 2019)
The current study explored neural correlates of the relationship between cognitive style and task switching processes. A task switching paradigm including object and verbal tasks was employed and neural responses were collected using fMRI. Behavioral and neural switch costs were correlated with individuals’ cognitive style preference scores. A total of thirty-five young adults participated in this study. Behavioral results showed that verbal preference scores were positively correlated with the switch cost in the object task. Neural responses in the object task showed a positive relationship between object style preference and the neural switch cost in the posterior cingulate cortex/precuneus and left intraparietal sulcus. In addition, an interaction between the object and verbal preferences was found in the angular gyrus during the object task. These results show how the individual differences in cognitive style preference during task switching could be linked to individual variations in neural responses. These findings suggest that cognitive style preference may be related to cognitive control through attentional resource allocation, and selection, and the processing of target- and distractor-relevant information during task switching. KCI Citation Count: 0